Comprehensive geriatric assessment in elderly outpatients with dementia - Aliberti,Márlon Juliano Romero (2007)
Abstract Dementia is a common disabling disease in the elderly. In such patients, general health conditions may worsen the functional decline and loss of autonomy. The Comprehensive Geriatric Assessment (CGA) is a validated and recommended instrument for multidimensional evaluation of the aged. Nonetheless, it has yet to be assessed in demented patients. Objectives: To analyze the functional, emotional and clinical status in elderly with dementia measured by the CGA. We also compared the results obtained in the same patients stratified for severity of dementia. Methods: Transversal study with demented elderly outpatients. Subjects were evaluated by the CGA consisting of clinical data, Clinical Dementia Rating, performance-oriented mobility assessment of gait and balance (POMA), Cornell scale for depression, activities of daily living, Mini Mental Status Examination (MMSE), Mini Nutritional Assessment, Whispered and Snellen Test. Results: Fifty-two patients with mean age of 77 years were evaluated. Majority of patients had Alzheimer disease (77%). Depression was the most prevalent comorbidity. The POMA score was related to the number of falls in the previous year. Also, there was correlation between complaints of visual and hearing impairment and the results on the Snellen and Whispered Tests. Regarding severity, 56% presented mild, 33% moderate and 11% severe condition. Patients with moderate/severe dementia had less leisure activities, greater risk of falls, along with worse performance on the MMSE, POMA and activities of daily living. Conclusions: The CGA was applied in demented elderly with the help of their caregivers, and was able to better characterize patient state of health. Subjects with moderate/severe dementia obtained poor results in several assessed criteria.